2019
DOI: 10.3390/nu11123030
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, but Not Perceived Food Environment, Is Associated with Diet Quality in French-Speaking Canadians from the PREDISE Study

Abstract: The objectives were to assess whether social support for healthy eating and perceived food environment are associated with diet quality, and to investigate if sociodemographic characteristics moderate these associations. A probability sample of French-speaking adults from the Province of Québec, Canada, was recruited in the context of the PREDISE study. Participants reported their perceptions of supportive and non-supportive actions related to healthy eating from close others at home and outside of home (n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Moreover, it has also been suggested that the community-based participatory research approach has led to sustained improvements in the dietary quality of the foreign population [ 70 ]. In line with our results, most studies have shown that social support is usually associated with better diet quality [ 71 , 72 , 73 ]. It should be noted that social support may be a significant resilience resource, as individuals may rely upon their work colleagues, family, or friends [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it has also been suggested that the community-based participatory research approach has led to sustained improvements in the dietary quality of the foreign population [ 70 ]. In line with our results, most studies have shown that social support is usually associated with better diet quality [ 71 , 72 , 73 ]. It should be noted that social support may be a significant resilience resource, as individuals may rely upon their work colleagues, family, or friends [ 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…The social food environment, defined as the foodrelated interactions between friends, family and peers, (12) has a major influence on individuals' intent and actual food behaviour (13) . The social food environment, including social norms, networks and contexts that promote the adoption of unhealthy dietary behaviour, is a potential underlying factor for the development of obesity (14) .…”
Section: Social Factors Food Environment Photovoice Dietary Behaviour...mentioning
confidence: 99%
“…In a recent systematic review, perceived healthy food environments were positively associated with healthy dietary habits [ 59 ]. However, there is a lack of studies assessing the link between diet quality and perceived food environment [ 14 , 60 , 61 , 62 ]. This current study measured diet quality using feasible and valid assessment tools, including a short food frequency survey (sHEI) [ 31 ] and a food liking survey [ 35 ].…”
Section: Discussionmentioning
confidence: 99%